The effect of corporate performance on the stocks in the companies doing IPO - - Suherman; Danni Winadi; Gatot Nazir Ahmad (Universitas Hayam Wuruk Perbanas, 2016)
This study tries to (1)to examine the difference of corporate social performance (CSP) between the old IPO firms and the new IPO firms, and (2)to investigate the influence of corporate social performance (CSP) on stock return. Corporate social performance (CSP) is measured using NH approach and stock return is measured using cumulative abnormal returns (CAR) and holding-period returns (HPR). The sample covers 75 IPO firms listed on the Indonesia Stock Exchange between 2011 and April 2015. Our study employs independent sample test and ordinary least square (OLS) regression to analyze the research models. The results show that 1) there is significant difference in corporate social performance (CSP) between the old IPO firms and the new IPO firms, and 2)CSP has positive and significant effect on stock return, controlling for firm size, firm growth, institutional ownership and managerial ownership. Robustness tests support the results. Investor should pay much more attention on the old IPO firms and corporate social performance (CSP). Firms that are going to sell IPO stocks, specifically for young firms, should concern more on social responsibilities.